Smokers can quit regardless of motivation stage in a worksite dmoking cessation programme in Malaysia - Yasin, Siti Munira; Retneswari, Masilamani; Moy, Foong Ming; Koh, David; Isahak, Marzuki (West Asia Organization for Cancer Prevention, 2011)
Background: There is an unclear relationship between smoker's early motivation and success rates. Here we aimed to explore the correlates of motivation and smoking abstinence and relapse in worksite smoking cessation programmes. Methods: This prospective cohort study involved employees from two major public universities in Malaysia. Participants were actively recruited into a smoking cessation programme. At the start of treatment, participants were administered a questionnaire on sociodemographic variables, smoking habits and `stage of change'. Behaviour therapy with free nicotine replacement therapy (NRT) was given as treatment for two months. A similar stage of change questionnaire was given at six months, and their smoking status was determined. Results: There were 185 smokers from both Universities, who joined the programme. At six months, 24 smokers reported sustained abstinence while the others had relapsed. Prior to the programme, the majority of smokers were seriously planning on quitting (59.5- preparation stage), but over a third had no plans to quit (35.5- contemplation stage). There was no significant difference noted in changes of motivation stage among the relapsers and the non quitters. In addition, logistic regression showed that sustained abstinence was not predicted by pre-session motivation stage, but this did predict higher relapse for the participants, compared to those in the preparation stage. Conclusion: It is possible to help smokers in the lower motivation groups to quit, provided extra caution is taken to prevent relapse. Healthcare providers' recruitment strategies for cessation programmes should thus encompass smokers in all motivation stages.